All about people! - Caio Nery (Journal of the Foot & Ankle)
The use of Artificial Intelligence (AI) across a wide range of human activities has been growing rapidly in recent years, becoming an indispensable tool, and science is no exception. However, concern is rising within the academic and scientific communities regarding the misuse of Generative AI in producing scientific papers. Key concerns include ethical and moral issues, along with the growing risk that it may soon become impossible to distinguish between human-generated and AI-generated content. This challenge is made even greater by the phenomenon known as AI “hallucination,” where the system, lacking reliable information, produces entirely fabricated material (texts and data). In addition, AI learning systems are becoming increasingly complex and opaque, making it harder for humans to fully understand and oversee them.